Nutritional experiences in head and neck cancer patients. (30th September 2019) - Sandmæl, Jon Arne; Sand, Kari; Bye, Asta; Solheim, Tora Skeidsvoll; Oldervoll, Line; Helvik, Anne‐Sofie
Abstract: Objective: Extensive research has documented the negative nutritional impact of head neck cancer (HNC) treatment, but few studies have addressed the patients' experiences. The purpose of this study was to describe how patients with HNC experience the nutritional situation and perceive nutritional support from diagnosis to the post‐treatment phase. Methods: Patients with HNC were recruited from a randomised pilot study. Individual interviews were conducted after radiotherapy with 10 participants aged 49 – 70 years and analysed by qualitative content analysis. Results: Undergoing surgery was experienced as a poor nutritional starting point for the upcoming radiotherapy. During radiotherapy, increasing side effects made the participants customise their meals to improve food intake. About halfway through radiotherapy, virtually no food intake was experienced and hospital admissions and initiations of tube‐feeding occurred in this period. Oral nutritional supplements were recommended for all, but eventually became unbearable to ingest. When radiotherapy was finally completed, the participants felt discouraged about the persistent side effects preventing them from resume eating. The participants missed tailored information about development of side effects and involvement of a dietitian when reflecting on the treatment‐period. Conclusion: The comprehensive nutritional problems experienced by patients with HNC require early nutritional assessments and improved individually tailored nutritional support.